2000
DOI: 10.1002/1520-6866(2000)20:6<329::aid-tcm2>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic, hematoxic, pathological, and biochemical effects of hexane on Swiss albino rats

Abstract: In the present study, the genotoxic, hematoxic effects, and their relation with pathological and biochemical parameters of hexane were investigated. Cytogenetic evaluation performed on the bone marrow indicated that chromosome aberrations increased at both hexane doses in relation to the negative controls. Decreased hematocrit, hemoglobin concentrations, and mean corpuscular volume were observed on the whole blood counts. Conjugated dienes (CD), glutathione (GSH), alanine aminotransferase (ALT), aspartate amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Hepatotoxicity was also confirmed by cellular histological examination. In conclusion, Egeli et al (2000) suggested that hexane is a genotoxic and hemotoxic agent leading to chromosome aberrations and lipid peroxidation in the exposed groups [92].…”
Section: N-hexane Metabolic Pattern Excretion and Toxicitymentioning
confidence: 85%
See 1 more Smart Citation
“…Hepatotoxicity was also confirmed by cellular histological examination. In conclusion, Egeli et al (2000) suggested that hexane is a genotoxic and hemotoxic agent leading to chromosome aberrations and lipid peroxidation in the exposed groups [92].…”
Section: N-hexane Metabolic Pattern Excretion and Toxicitymentioning
confidence: 85%
“…For example, the toxicological dossier on n-hexane from the French National Institute for Research and Occupational Safety (INRS, 2019) reported that n-hexane causes chromosomal aberrations and sperm abnormalities in rats after inhalation exposure [54]. Egeli et al (2000) studied genotoxic and hemotoxic effects in rats, subcutaneously exposed to hexane (not specifying whether it was n-hexane or technical hexane) and compared them with a non-exposed group and a positive control group exposed to benzene [92]. Although the genotoxic effect of benzene was more pronounced, hexane (0.125 and 0.250 mL/kg in single dose for 3 months) showed a significant clastogenic effect in rat bone marrow cells, with an increase in chromosomal aberrations compared to unexposed controls.…”
Section: N-hexane Metabolic Pattern Excretion and Toxicitymentioning
confidence: 99%
“…For example, the toxicological dossier on n -hexane from the French National Institute for Research and Occupational Safety (INRS, 2019) reported that n -hexane causes chromosomal aberrations and sperm abnormalities in rats after inhalation exposure [ 53 ]. Egeli et al (2000) studied genotoxic and hemotoxic effects in rats subcutaneously exposed to hexane (not specifying whether it was n -hexane or technical hexane) and compared them with a non-exposed group and a positive control group exposed to benzene [ 84 ]. Although the genotoxic effect of benzene was more pronounced, hexane (0.125 and 0.250 mL/kg in a single dose for three months) showed a significant clastogenic effect in rat bone marrow cells, with an increase in chromosomal aberrations compared to unexposed controls.…”
Section: The Toxicological Assessment Of Hexane As Extraction Solventmentioning
confidence: 99%
“…Hepatotoxicity was also confirmed by cellular, histological examination. In conclusion, Egeli et al (2000) suggested that hexane is a genotoxic and hemotoxic agent leading to chromosome aberrations and lipid peroxidation in the exposed groups [ 84 ].…”
Section: The Toxicological Assessment Of Hexane As Extraction Solventmentioning
confidence: 99%
See 1 more Smart Citation